Międzynarodowa ochrona wolności związkowej - Michalska, Anna (Wydział Prawa i Administracji UAM, 1982)
Resume of the regulation of general treaties, both universal and regional concerning freedom of associations and of assembly is presented in the introductory remarks of the author. Treaties concerning freedom of trade unions undersigned within the International Labor Organization are hereinafter analyzed. These are: Convention nr 11 concerning the Right of Association in Agriculture, nr 84 concerning the Right of Association in Non-Metroplitan Territories, nr 87 concerning Freedom of Association and Protection of the Right to Organize, nr 98 concerning the Application of the Principles of the Right to Organize and Bargain Collectively, nr 135 concerning Protection and Facilities to be Afforded to Workers' Representatives in the Undertaking, nr 141 concerning the Organization of Rural Workers and Their Role in Social and Economic Developement. Special procedure concerning international protection of trade union rights is discussed in final part of the article. Action of the Committee of Union Freedoms and procedure before the Investigation and Conciliatory Commission in matters of freedom of trade unions is presented. This special mechanism provides, for many reasons, for completion of general procedures of control which are applicable to all conventions of ILO. Being founded on the plaints it permits to examine the questions which could escape control which is based on examination of governmental reports. This control can be applied even with regard to the countries that have not ratified the conventions of freedom of trade unions and in consequence, as far as it applies to these countries, it allows to take up such problems which were found to be difficult to examine, and their solutions were timely and less profound than expected whithin the scope of general procedures. The control is founded rather on general principles in question of union freedoms, than on detailed guidelines of the respective conventions in that matter therefore it allows for more flexibility and can be more easily applied and extended in varying circumstances.
International Protection of Trade Union's Sovereignty